A Study on the NEP 2020 and Status of School Teachers - Anand, Amit (ELITE JOURNAL, 2023)
ABSTRACT Education is the backbone of a nation. It paves the way for all round development including peace, progress and prosperity of a man, society and Country . With the changing scenario of Global world a more meaningful technology-based education system became the crying need of the hour. Hence National Education policy 2020 was launched by the Central Govt of India on 29th July 2020 to meet the Challenges of modern society. After a gap of nearly 34Years NEP 2020 will now definitely prove the most effective and outstanding education policy of modern India. Only a value-based education system can bring basic changes in old education and examination system. Now multidisciplinary education system of GlobalStandards and National Research Foundation will be created as an apex body for fostering a strong research culture among teachers of today. More research facilities would be provided to improve their capacity and capability . This new policy provides for reforms at all levels of education form school to higher education. It focuses on Early Childhood Care, Reform the current exam system, Strenghten techer-training and Restructure the education regulatory framework. The role of Teacher is to shape the minds of the younger generation and hence teachers must be passionate, motivated and well qualified. Provisions have been made even for online learning as an alternative to regular classroom interaction between teachers and students for better understanding. Detailed provisions of New Education Policy has been well documented. The present conceptual research paper is to study the objective of New Education Policy 2020, its features and Role of Teachers. The students-teacher interaction is much significant in the new education era. Keywords: Features of NEP , Role of Teacher, Restructure.